SARS-CoV-2 infection induces activation of ferroptosis in human placenta - Wang, Bingbing; Shen, Wei-Bin; Yang, Peixin; Turan, Sifa (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis, a regulated non-apoptotic form of cell death, has been implicated in the response to varied types of infectious agents including virus. In this study, we sought to determine whether SARS-CoV-2 infection can induce activation of ferroptosis in the human placenta. We collected placentas from 23 pregnant females with laboratory-confirmed SARS-CoV-2 following delivery and then used RNA in situ hybridization assay for detection of viral positive-sense strand (PSS) to confirm that these placentas have been infected. We also used immunohistochemistry assay to assess expression levels of acyl-CoA synthetase long-chain family member 4 (ACSL4), an essential executioner of ferroptosis in the same specimens. Our results showed that ACSL4 expression was significantly increased in the group with positive PSS staining compared to their negative counterparts (p = 0.00022). Furthermore, we found that there was a positive trend for increased PSS staining along with increased ACSL4 expression. Our study supports that ferroptosis is activated in the response to SARS-CoV-2 infection in the human placenta, highlighting a molecular mechanism potentially linking this coronavirus infection and pathogenesis of adverse pregnancy outcomes.